Description of the postmarsupial manca stages of Armadillidium granulatum (Crustacea, Isopoda, Oniscidea). Issue 1 (2nd January 2019) - Zecchini, Alice; Montesanto, Giuseppe
ABSTRACT: The development of the postmarsupial manca stages of Armadillidium granulatum Brandt, 1833 was studied in detail by morphological analysis. Ovigerous females were reared separately under controlled conditions, allowing us to follow the stages of development from release from the marsupium until the appearance of the first juvenile stage, identified by the full development of the seventh pair of pereopods. Each newborn was followed to record the subsequent moults that identify the three postmarsupial manca stages. Manca stage M I had a mean duration of 6 h, manca stage M II 15 days, and manca stage M III 32 days. The cephalothorax width was measured to provide a growth measure for each stage. The mean values of the cephalothorax width were: 0.512 mm (± 0.083 SD) for M I, 0.677 mm (± 0.058 SD) for M II and 1.194 mm (± 0.079 SD) for M III. The morphological modifications in the three postmarsupial manca stages were described, the body parts illustrated, and SEM images taken. The distinguishing characteristics among mancas were discussed, and comparisons made with manca stages of other terrestrial isopod species.